Activated microglia release β−galactosidase that promotes inflammatory neurodegeneration - Kitchener, Emily J. A.; Dundee, Jacob M.; Brown, Guy C. (Frontiers in Aging Neuroscience, 2024)
b-galactosidase is a lysosomal enzyme that removes terminal galactose residues from glycolipids and glycoproteins. It is upregulated in, and used as a marker for, senescent cells. Microglia are brain macrophages implicated in neurodegeneration, and can upregulate bgalactosidase when senescent. We find that inflammatory activation of microglia induced by lipopolysaccharide results in translocation of b-galactosidase to the cell surface and release into the medium. Similarly, microglia in aged mouse brains appear to have more bgalactosidase on their surface. Addition of b-galactosidase to neuronal-glial cultures causes microglial activation and neuronal loss mediated by microglia. Inhibition of b-galactosidase in neuronal-glial cultures reduces inflammation and neuronal loss induced by lipopolysaccharide. Thus, activated microglia release b-galactosidase that promotes microglial-mediated neurodegeneration which is prevented by inhibition of b-galactosidase.